Employee Performance is Assessed in Terms of Spiritual Intelligence, Work Ethic, Islamic Leadership, and Religiosity - Henny Puspitosari Utami; Istiatin Istiatin; Yunia Wahdiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of spiritual intelligence, work ethic, Islamic leadership, and religiosity on employee performance at the Kartasura Community Health Center. The study used a quantitative approach with a survey method. The population in this study were all 104 employees of the Kartasura Community Health Center who were also used as research samples using a saturated sampling technique. Data collection was carried out using a questionnaire that had been tested for validity and reliability. Data analysis used multiple linear regression with the help of the SPSS program. The results showed that spiritual intelligence had a positive and significant effect on employee performance with a t-value of 2.736 and a significance of 0.007. Work ethic had a positive and significant effect on employee performance with a t-value of 2.262 and a significance of 0.026. Religiosity also had a positive and significant effect on employee performance with a t-value of 2.387 and a significance of 0.001. Meanwhile, Islamic leadership did not have a significant effect on employee performance with a t-value of 0.150 and a significance of 0.881. The research findings show that internal employee factors in the form of spiritual intelligence, work ethic, and religiosity have an important role in improving employee performance, while Islamic leadership has not had a significant influence on employee performance at the Kartasura Community Health Center.